Unlocking the potential of other effective area-based conservation measures (OECMs) for achieving conservation targets: A global scoping review - Dimitra Petza; Eva Amorim; Emna Ben Lamine; Francesco Colloca; Esther Dominguez Crisóstomo; Erika Fabbrizzi; Simonetta Fraschetti; Ibon Galparsoro; Sylvaine Giakoumi; Maren Kruse; Vanessa Stelzenmüller; Stelios Katsanevakis (Ambio, 2026)
Other Effective Area-based Conservation Measures (OECMs), introduced by the Convention on Biological Diversity (CBD), refer to areas outside formal protected-area networks that deliver effective and enduring in situ biodiversity conservation. This scoping review systematically examined global approaches to identifying and evaluating potential OECMs. Analysing 99 studies covering 694 case studies and 237 000 potential sites, we found that potential OECMs are widespread, particularly in Asia and terrestrial environments, with most initiatives led by the environmental sector. Assessments relied largely on qualitative expert knowledge, with limited application of analytical methods. Although CBD criteria were commonly applied, contributions of related to ecosystem services and socio-cultural values were often overlooked. Effectiveness evaluations showed considerable uncertainty, with over one-third of case studies reporting inadequate evidence of conservation outcomes. The review emphasises the need for standardised assessment methodologies, improved decision-support tools, and socio-cultural integration to enhance OECM recognition, particularly under the 30 × 30 conservation biodiversity target.

Trophic ecology of the deep-sea skate Dipturus oxyrinchus (Linnaeus, 1758) in the bathyal food web of the central Mediterranean Sea - Martina Arcioni; Isabella D'Ambra; Salvatrice Vizzini; Danilo Scannella; Monica Calabrò; Fabio Falsone; Michele Luca Geraci; Marco Oliverio; Sergio Vitale; Germana Garofalo; Gioacchino Bono; Francesco Colloca (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Living on the Extinction Edge: Resilience to Fishing and Rebound Potential of the Mediterranean Elasmobranchs - Stefano Moro; Salvatore Valente; Martina Arcioni; Fabio Falsone; Danilo Scannella; Michele Luca Geraci; Manfredi Di Lorenzo; Giacomo Milisenda; Fabrizio Serena; Francesco Colloca (Fish and Fisheries, 2025)
Mediterranean elasmobranchs are experiencing significant declines due to intense fishing activities, making the region a global hotspot for elasmobranch conservation concerns. These declines are worsened by limited fisheries data, constraining stock assessments and evidence‐based management. Demographic models based on life history parameters (e.g., survival rate, age‐at‐maturity, litter size and longevity) offer critical alternatives for estimating population productivity in data‐poor contexts. In this study, we estimated the intrinsic rate of population increase () for 82 stocks across 51 species of Mediterranean sharks and rays to assess their relative capacity for recovery under hypothetical sustainable exploitation scenarios. Using demographic modelling and updated life history data, we provide a comparative analysis of species‐specific productivity and identify those with the lowest recovery potential. Many IUCN‐listed threatened species exhibited very low rebound potential, highlighting their vulnerability to fishing. Significant data gaps, especially for pelagic and deep‐sea taxa, underscore the need for targeted life history research. Our results also showed how the rebound potential can provide valuable insight for data‐deficient species, supporting informed assessments with limited biological input. Furthermore, we confirmed that age‐at‐maturity is a valid proxy of when other parameters are unavailable. This study delivers a comprehensive, regional‐scale productivity baseline for Mediterranean elasmobranchs, providing essential input for prioritising species‐specific conservation actions, guiding fishery policy development and improving regional compliance with international conservation frameworks. By addressing critical data limitations, our approach enhances the scientific foundation necessary for the sustainable management and recovery of shark and ray populations in the Mediterranean Sea.

Assessing the relevance of sharks and rays for Mediterranean EU fisheries to support a transition from species exploitation to species conservation - Francesco Colloca; Martina Arcioni; Francesca Acampa; Salvatore Valente; Daniele Ventura; Manfredi Di Lorenzo; Giacomo Milisenda; Stefano Moro (Reviews in Fish Biology and Fisheries, 2025)

New findings into the genetic population structure of two commercially valuable and threatened sharks, Mustelus mustelus (Linnaeus, 1758) and M. punctulatus (Risso, 1827), allow refining management strategy in the Central Mediterranean Sea - Matteo Barbato; Sara Bonanomi; Diego Borme; Ilija Ćetković; Francesco Colloca; Manfredi Di Lorenzo; Ilaria A. M. Marino; Carlotta Mazzoldi; Ana Pešić; Antonello Sala; Lorenzo Zane; Massimo Mezzavilla (Frontiers in Marine Science, 2025)
Elasmobranch species are the direct or accidental catch of fisheries and can have a commercial importance. In the Mediterranean Sea, a long-term period of overfishing brought several demersal elasmobranchs to be depleted and threatened by extinction, due to vulnerability related to their life history traits. In such exploited species, information on genetic diversity and connectivity is lacking and should be collected to identify management units. In this study, we focused on two threatened smooth-hound species, Mustelus Mustelus (Linnaeus, 1758) and M. punctulatus (Risso, 1827), whose abundance and distribution showed a decline at the Mediterranean regional level in the last century. Thanks to an opportunistic yet extensive sampling, we obtained the largest subregional collection of specimens for genetic analysis so far. In total, 86 and 214 specimens of M. mustelus and M. punctulatus were collected between 2016 and 2020 in the Adriatic Sea and the Strait of Sicily. We assessed the population genetic structure typing 17 microsatellites and sequencing part of the mitochondrial control region in both species. We observed a substantial nuclear and mitochondrial genetic structure when accounting for the geographical sampling area for both species. Our results indicate the presence of at least two genetic stocks for each of the two species: one in the Strait of Sicily and the other in the Adriatic Sea. This study provides valuable data that should be integrated into a broader approach to define management units, improving the development of an effective management strategy for these threatened species in the Central Mediterranean Sea.

Atlantis end-to-end modeling to explore ecosystem dynamics in the Strait of Sicily, Central Mediterranean Sea - Matteo Sinerchia; Fabio Fiorentino; Francesco Colloca; Andrea Cucco; Germana Garofalo; Angelo Perilli; Giovanni Quattrocchi; Elizabeth A. Fulton (Environmental Modelling & Software, 2025)

Testing best practices in small scale fisheries management: Evidence from a collaborative intervention in two marine protected areas of the central Mediterranean Sea - Serena Zampardi; Claudia Scianna; Antonio Calò; Katie Hogg; Marco Ranù; Giorgio Aglieri; Emanuela Di Meglio; Maria Cristina Mangano; Giulia Prato; Teresa Romeo; Francesco Colloca; Giacomo Milisenda; et al. (Ocean & Coastal Management, 2024)

Exploring the effects of temperature on demersal fish communities in the Central Mediterranean Sea using INLA-SPDE modeling approach - Claudio Rubino; Giada Adelfio; Antonino Abbruzzo; Mar Bosch-Belmar; Manfredi Di Lorenzo; Fabio Fiorentino; Vita Gancitano; Francesco Colloca; Giacomo Milisenda (Environmental and Ecological Statistics, 2024)
Climate change significantly impacts marine ecosystems worldwide, leading to alterations in the composition and structure of marine communities. In this study, we aim to explore the effects of temperature on demersal fish communities in the Central Mediterranean Sea, using data collected from a standardized monitoring program over 23 years. Computationally efficient Bayesian inference is performed using the integrated nested Laplace approximation and the stochastic partial differential equation approach to model the spatial and temporal dynamics of the fish communities. We focused on the mean temperature of the catch (MTC) as an indicator of the response of fish communities to changes in temperature. Our results showed that MTC decreased significantly with increasing depth, indicating that deeper fish communities may be composed of colder affinity species, more vulnerable to future warming. We also found that MTC had a step-wise rather than linear increase with increasing water temperature, suggesting that fish communities may be able to adapt to gradual changes in temperature up to a certain threshold before undergoing abrupt changes. Our findings highlight the importance of considering the non-linear dynamics of fish communities when assessing the impacts of temperature on marine ecosystems and provide important insights into the potential impacts of climate change on demersal fish communities in the Central Mediterranean Sea.

Habitat loss and small‐scale fishery: A controversial issue - Chiara Silvestrini; Alberto Colletti; Antonio Di Franco; Francesco Colloca; Giacomo Milisenda; Serena Zampardi; Maria Cristina Mangano; Giorgio Aglieri; Marco Ranù; Gianluca Liguori; Roberto Danovaro; Federica Foglini; et al. (Marine Ecology, 2024)
Fishery is one of the most impacting human activities and is responsible for habitat loss in marine systems. While the effects of large‐scale fisheries have been largely investigated, impacts of small‐scale fisheries (SSF) on seafloor integrity are more often assumed than quantitatively investigated. We carried out a literature review at global scale, resulting in 19 studies with quantitative data on sessile benthic bycatch and only one documenting habitat loss driven by SSF. We also conducted a fine‐scale assessment within a Mediterranean partially protected area (PPA). Results showed that 513 m 2 of the Posidonia oceanica meadow are removed annually by local SSF within the PPA, considering bycatch, fishing effort, and shoot density. Knowledge on fishing effort and fine‐scale mapping is critical to assess habitat loss, suggesting the need for specific recommendations for eco‐sustainable local fisheries.

Deficiencies in monitoring practices of marine protected areas in southern European seas - Sylvaine Giakoumi; Katie Hogg; Manfredi Di Lorenzo; Nicolas Compain; Claudia Scianna; Giacomo Milisenda; Joachim Claudet; Dimitrios Damalas; Pierluigi Carbonara; Francesco Colloca; Athanasios Evangelopoulos; Igor Isajlović; et al. (Journal of Environmental Management, 2024)

Mediterranean fish communities are struggling to adapt to global warming. Evidence from the western coast of Italy - Salvatore Valente; Stefano Moro; Manfredi Di Lorenzo; Giacomo Milisenda; Luigi Maiorano; Francesco Colloca (Marine Environmental Research, 2023)

Sharks Do Not Always Grow Slowly: Tagging Data Reveal a Different Pattern of Growth, Longevity and Maturity for Threatened Smooth-Hounds in the Central Mediterranean Sea - Gabriele Boscolo Palo; Manfredi Di Lorenzo; Salvatore Gancitano; Sergio Ragonese; Carlotta Mazzoldi; Francesco Colloca (Journal of Marine Science and Engineering, 2022)
Elasmobranchs are among the marine species more threatened by overfishing. Their conservation is often impaired by the lack of knowledge of species’ life history traits. We filled knowledge gaps on age and growth of two threatened smooth-hound sharks (Mustelus mustelus, Mm; Mustelus punctulatus, Mp) in the central Mediterranean Sea, combining standard vertebrae analysis with growth increment data from a tagging survey. Our data revealed that the two species grow at a faster rate than previously estimated using vertebrae reading only. The maximum age/size found was higher for Mm (16 years, 170 cm TL) than Mp (8 years, 120 cm TL), the first species attaining larger size-at-age than the second one. Mp reaches maturity at earlier ages (A50 3 years for both females and males) than Mm (A50 females: 4 years; males: 3 years). The use of the tag-recapture method to validate the growth rate, firstly derived by sectioned vertebrae readings, highlighted the presence of false check marks. The new estimates of growth and longevity have important implications for the assessment of natural mortality, productivity, and stock resilience to fishing pressure which, combined with the high site fidelity highlighted by tagging data, may have crucial implications for the conservation of these two threatened sharks in the Mediterranean Sea.

Interactive effects of fishing effort reduction and climate change in a central Mediterranean fishing area: Insights from bio-economic indices derived from a dynamic food-web model - Davide Agnetta; Fabio Badalamenti; Francesco Colloca; Gianpiero Cossarini; Fabio Fiorentino; Germana Garofalo; Bernardo Patti; Carlo Pipitone; Tommaso Russo; Cosimo Solidoro; Simone Libralato (Frontiers in Marine Science, 2022)
Disentangling the effects of mixed fisheries and climate change across entire food-webs requires a description of ecosystems using tools that can quantify interactive effects as well as bio-economic aspects. A calibrated dynamic model for the Sicily Channel food web, made up of 72 functional groups and including 13 fleet segments, was developed. A temporal simulation until 2050 was conducted to evaluate the bio-economic interactive effects of the reduction of bottom trawling fishing effort by exploring different scenarios that combine fishery and climate change. Our results indicate that direct and indirect effects produce a net increase in biomass of many functional groups with immediate decline of trawlers’ catches and economic incomes, followed by a long term increase mainly due to biomass rebuilding of commercial species which lasts 5-10 years after fishing reduction. Synergistic and antagonistic effects caused by changes in the fishing effort and in climate characterize a specific functional group’s response in biomass which, in turn, modulate also the catch and income of the other fleets, and especially of those sharing target resources. However, trawler’s intra-fleet competition is higher than the others fleet effects. In the medium term, the effects of fishing effort reduction are higher than those of climate change and seem to make exploitation of marine resources more sustainable over time and fishery processes more efficient by improving ecosystem health.

ClimateFish: A Collaborative Database to Track the Abundance of Selected Coastal Fish Species as Candidate Indicators of Climate Change in the Mediterranean Sea - Ernesto Azzurro; Tosca Ballerini; Chryssanthi Antoniadou; Giulia Domizia Aversa; Jamila Ben Souissi; Andrea Blašković; Valentina Cappanera; Marina Chiappi; Maria-Francesca Cinti; Francesco Colloca; Ivan Cvitković; Manuela D’Amen; et al. (Frontiers in Marine Science, 2022)

Mesoscale productivity fronts and local fishing opportunities in the European Seas - Jean‐Noël Druon; Didier Gascuel; Maurizio Gibin; Antonella Zanzi; Jean‐Marc Fromentin; Francesco Colloca; Pierre Hélaouët; Marta Coll; Alessandro Mannini; Joanna K Bluemel; Chiara Piroddi; Francois Bastardie; et al. (Fish and Fisheries, 2021)
This study evaluates the relationship between both commercial and scientific spatial fisheries data and a new satellite‐based estimate of potential fish production (Ocean Productivity available to Fish, OPFish) in the European Seas. To construct OPFish, we used productivity frontal features derived from chlorophyll‐ a horizontal gradients, which characterize 10%–20% of the global phytoplankton production that effectively fuels higher trophic levels. OPFish is relatively consistent with the spatial distribution of both pelagic and demersal fish landings and catches per unit of effort (LPUEs and CPUEs, respectively). An index of harvest relative to ocean productivity (H P index) is calculated by dividing these LPUEs or CPUEs with OPFish. The H P index reflects the intensity of fishing by gear type with regard to local fish production. Low H P levels indicate lower LPUEs or CPUEs than expected from oceanic production, suggesting over‐exploitation, while high H P levels imply more sustainable fishing. H P allows comparing the production‐dependent suitability of local fishing intensities. Our results from bottom trawl data highlight that over‐exploitation of demersal species from the shelves is twice as high in the Mediterranean Sea than in the North‐East Atlantic. The estimate of H P index by dominant pelagic and demersal gears suggests that midwater and bottom otter trawls are associated with the lowest and highest overfishing, respectively. The contrasts of fishing intensity at local scales captured by the H P index suggest that accounting for the local potential fish production can promote fisheries sustainability in the context of ecosystem‐based fisheries management as required by international marine policies.

The use of fishers’ Local Ecological Knowledge to reconstruct fish behavioural traits and fishers’ perception of conservation relevance of elasmobranchs in the Mediterranean Sea - MATTEO BARBATO; CLAUDIO BARRÍA; ANDREA BELLODI; SARA BONANOMI; DIEGO BORME; ILIJA ĆETKOVIĆ; FRANCESCO COLLOCA; ANA I. COLMENERO; FABIO CROCETTA; FRANCESCO De CARLO; EGEMEN DEMİR; MANFREDI Di LORENZO; et al. (Mediterranean Marine Science, 2021)
The Mediterranean Sea has a long-lasting history of fishery exploitation that, together with other anthropogenic impacts, has led to declines in several marine organisms. In particular, elasmobranch populations have been severely impacted, with drastic decreases in abundance and species diversity. Based on their experience, fishers can provide information on marine species occurrence, abundance and behavioural traits on a long-term scale, therefore contributing to research on the poorly studied biological aspects of elusive or rare elasmobranch species. In this study, for the first time, the use of the Local Ecological Knowledge (LEK) of fishers was applied to study the behavioural traits of sharks, rays and skates in 12 FAO-GFCM geographical sub-areas (GSAs) of the Mediterranean Sea. This study found both new insight and proved the reliability of LEK-based catch seasonality, reflecting seasonal movements, by comparing LEK-based findings and available literature on five elasmobranch taxa (Mustelus spp., Squalus acanthias, Raja spp., Myliobatis aquila and Scyliorhinus stellaris) in the Adriatic Sea and 7 taxa (Mustelus spp., Raja spp., Prionace glauca, Scyliorhinus canicula, Torpedo spp., Pteroplatytrygon violacea and Isurus oxyrinchus) in the remaining Mediterranean GSAs. In addition, LEK provided new insights into a novel comprehensive representation of species aggregations (Mustelus spp., S. acanthias, M. aquila and S. canicula) in the sampled GSAs and supplied the first descriptions of the size, number of individuals and sex composition of the aggregations. When the limits and shortcomings of LEK-based research are considered, this methodology can be a complementary and cost-effective tool used to study elasmobranchs in either a data-poor scenario or a scenario in which a baseline is missing. LEK can also be useful for the evaluation and inclusion of fishers’ perceptions on bottom-up management and to provide important evidence for conservation plans.

Identifying Persistent Hot Spot Areas of Undersized Fish and Crustaceans in Southern European Waters: Implication for Fishery Management Under the Discard Ban Regulation - Giacomo Milisenda; Germana Garofalo; Fabio Fiorentino; Francesco Colloca; Francesc Maynou; Alessandro Ligas; Claudia Musumeci; Luís Bentes; Jorge M. S. Gonçalves; Karim Erzini; Tommaso Russo; Lorenzo D’Andrea; et al. (Frontiers in Marine Science, 2021)
The recent establishment of the “landing obligation” under the reformed EU Common Fishery Policy has the twofold objective of reducing the excessive practice of discarding unwanted catch at sea and encouraging more selective and sustainable fisheries. Within this context, the awareness of the spatial distribution of potential unwanted catches is important for devising management measures aimed to decrease discards. This study analyzed the distribution of Hot Spot density areas of demersal fish and crustaceans below the Minimum Conservation Reference Size (MCRS) in four different southern European seas: continental Portuguese coast, Catalan Sea, South of Sicily, Liguria and northern Tyrrhenian Seas using both bottom trawl survey data and information on the spatial distribution of commercial fisheries. Critical areas for discarding were identified as zones where the highest densities of individuals below MCRS were consistently recorded throughout a series of years. Results clearly showed a patchy distribution of undersized individuals in each investigated area, highlighting the overlap between high density patches of both discards and fishing effort. The present findings provide a relevant knowledge for supporting the application of spatial-based management actions, such as the designation of Fisheries Restricted Areas (FRAs), in order to minimize the by-catch of undersized specimens and improve the sustainability of demersal fisheries.

Using Local Ecological Knowledge of Fishers to Reconstruct Abundance Trends of Elasmobranch Populations in the Strait of Sicily - Francesco Colloca; Virginia Carrozzi; Andrea Simonetti; Manfredi Di Lorenzo (Frontiers in Marine Science, 2020)

British sharks in Sicily: records of long distance migration of tope shark (Galeorhinus galeus) from North-eastern Atlantic to Mediterranean Sea. - FRANCESCO COLLOCA; DANILO SCANNELLA; MICHELE LUCA GERACI; FABIO FALSONE; GIUSTO BATISTA; SERGIO VITALE; MANFREDI DI LORENZO; GIOACCHINO ΒΟΝΟ (Mediterranean Marine Science, 2019)
The study reports information about the recapture of two tagged adult females of tope shark, Galeorhinus galeus (Linnaeus 1758), in the central Mediterranean Sea (south coasts of Sicily) in 2014 and 2017. The two females were tagged in North-East Atlantic, respectively in Scotland in 2009 and Ireland in 2015. The Scottish specimen was a 175 cm female increasing of about 10 kg in body weight and 37 cm in total length during its 1967 days at liberty (5.39 years). The Irish one, was a pregnant female of an estimated age of 15-17 year which spent 248 days at liberty increasing 14 cm during this period. The growth rate of the two specimens was therefore between 6.8 and 7.8 cm year-1, faster than the annual increments of adults suggested in previous studies. Previous tope recapture records in the Mediterranean Sea were limited to the Alboran Sea, coast of Valencia and the Algerian coasts. The two tope females recaptured in the Strait of Sicily provided the first evidence of long distance entrance of NE Atlantic tope in the Mediterranean Sea. The well known occurrence of mature females and juveniles in this area of the Mediterranean suggest the hypothesis of a migration of adults female from their feeding grounds in north eastern Atlantic to lower latitudes up to the Mediterranean Sea for parturition.

The North sector of the Strait of Sicily: a priority area for conservation in the Mediterranean Sea - Manfredi Di Lorenzo; Matteo Sinerchia; Francesco Colloca (Hydrobiologia, 2018)

Erratum to: Biomass HotSpot distribution model and spatial interaction of two exploited species of horse mackerel in the south-central Mediterranean Sea - Giacomo Milisenda; Germana Garofalo; Samia Fezzani; Okbi Rjeibi; Othman Jarboui; Bachra Chemmam; Luca Ceriola; Angelo Bonanno; Simona Genovese; Gualtiero Basilone; Roberta Mifsud; Valentina Lauria; et al. (Hydrobiologia, 2018)

Biomass HotSpot distribution model and spatial interaction of two exploited species of horse mackerel in the south-central Mediterranean Sea - Milisenda Giacomo; Garofalo Germana; Fezzani Samia; Rjeibi Okbi; Jarboui Othman; Chemmam Bachra; Ceriola Luca; Bonanno Angelo; Genovese Simona; Basilone Gualtiero; Mifsud Roberta; Lauria Valentina; et al. (Hydrobiologia, 2018)

Key Economic Characteristics of Italian Trawl Fisheries and Management Challenges - Evelina C. Sabatella; Francesco Colloca; Gianluigi Coppola; Fabio Fiorentino; Monica Gambino; Loretta Malvarosa; Rosaria Sabatella (Frontiers in Marine Science, 2017)

Recent Trends and Impacts of Fisheries Exploitation on Mediterranean Stocks and Ecosystems - Francesco Colloca; Giuseppe Scarcella; Simone Libralato (Frontiers in Marine Science, 2017)

Food preferences and rhythms of feeding activity of two co‐existing demersal fish, the longspine snipefish, Macroramphosus scolopax (Linnaeus, 1758), and the boarfish Capros aper (Linnaeus, 1758), on the Mediterranean deep shelf - Paolo Carpentieri; Natalia Serpetti; Francesco Colloca; Alessandro Criscoli; Giandomenico Ardizzone (Marine Ecology, 2016)
The feeding behaviour of two potentially competing species, the longspine snipefish, Macroramphosus scolopax , and the boarfish Capros aper was examined. While both species are very abundant along the Mediterranean coast and are regularly caught by demersal trawlers, they are of no commercial value. The diets of boarfish and longspine snipefish were investigated from samples collected between January 2001 and May 2002. Variations in the diet with fish size and season, as well as diet overlap and diversity were explored. Mysid shrimps, amphipods and gastropods were the most important food items in the diet of longspine snipefish. During ontogenetic development, M. scolopax occupies different trophic levels: the diet shifts from being predominantly composed of mysids ( Anchialina agilis , Lophogaster typicus , Erythrops sp., Leptomysis spp.) in the smaller longspine snipefish [ TL )] towards decapods ( Anapagurus laevis ) and amphipods ( Leucothoe incisa , Eusirus longipes , Hyperidea) in the larger individuals (>6.5 cm TL ). Crustacean decapods and copepods were the most important prey in the stomachs of boarfish. Mysids ( Lo. typicus ), euphausiids and nematodes were present in the larger individuals (>8 cm TL ). A more generalist diet, still containing copepods, crustacean decapods, gastropods ( Limacina retroversa ) and a large variety of amphipods ( e.g. Phtysica marina , Stenotoe bosphorana ) and mysids ( e.g. A. agilis , Leptomysis spp., Erythrops sp.), dominated the diet of C. aper between 2 and 8 cm TL . Diet overlap between longspine snipefish and boarfish was very low and the differences in stomach species diversity were explained by season and fish size.

From projected species distribution to food‐web structure under climate change - Camille Albouy; Laure Velez; Marta Coll; Francesco Colloca; François Le Loc'h; David Mouillot; Dominique Gravel (Global Change Biology, 2014)
Climate change is inducing deep modifications in species geographic ranges worldwide. However, the consequences of such changes on community structure are still poorly understood, particularly the impacts on food‐web properties. Here, we propose a new framework, coupling species distribution and trophic models, to predict climate change impacts on food‐web structure across the Mediterranean Sea. Sea surface temperature was used to determine the fish climate niches and their future distributions. Body size was used to infer trophic interactions between fish species. Our projections reveal that 54 fish species of 256 endemic and native species included in our analysis would disappear by 2080–2099 from the Mediterranean continental shelf. The number of feeding links between fish species would decrease on 73.4% of the continental shelf. However, the connectance of the overall fish web would increase on average, from 0.26 to 0.29, mainly due to a differential loss rate of feeding links and species richness. This result masks a systematic decrease in predator generality, estimated here as the number of prey species, from 30.0 to 25.4. Therefore, our study highlights large‐scale impacts of climate change on marine food‐web structure with potential deep consequences on ecosystem functioning. However, these impacts will likely be highly heterogeneous in space, challenging our current understanding of climate change impact on local marine ecosystems.

Rebuilding Mediterranean fisheries: a new paradigm for ecological sustainability - Francesco Colloca; Massimiliano Cardinale; Francesc Maynou; Marianna Giannoulaki; Giuseppe Scarcella; Klavdija Jenko; Josè Maria Bellido; Fabio Fiorentino (Fish and Fisheries, 2013)
In Mediterranean European countries, 85% of the assessed stocks are currently overfished compared to a maximum sustainable yield reference value (MSY) while populations of many commercial species are characterized by truncated size‐ and age‐structures. Rebuilding the size‐ and age‐structure of exploited populations is a management objective that combines single species targets such as MSY with specific goals of the ecosystem approach to fisheries management (EAF), preserving community size‐structure and the ecological role of different species. Here, we show that under the current fishing regime, stock productivity and fleet profitability are generally impaired by a combination of high fishing mortality and inadequate selectivity patterns. For most of the stocks analysed, a simple reduction in the current fishing mortality ( F cur ) towards an MSY reference value ( F MSY ), without any change in the fishing selectivity, will allow neither stock biomass nor fisheries yield and revenue to be maximized. On the contrary, management targets can be achieved only through a radical change in fisheries selectivity. Shifting the size of first capture towards the size at which fish cohorts achieve their maximum biomass, the so‐called optimal length, would produce on average between two and three times higher economic yields and much higher biomass at sea for the exploited stocks. Moreover, it would contribute to restore marine ecosystem structure and resilience to enhance ecosystem services such as reservoirs of biodiversity and functioning food webs.

Trends in population dynamics and fishery of Parapenaeus longirostris and Nephrops norvegicus in the Tyrrhenian Sea (NW Mediterranean): the relative importance of fishery and environmental variables - Alessandro Ligas; Paolo Sartor; Francesco Colloca (Marine Ecology, 2011)
Temporal variation in the population abundance of the deep‐water rose shrimp, Parapenaeus longirostris (Lucas, 1846) (Decapoda, Penaeidae), and the Norway lobster, Nephrops norvegicus (Linnaeus, 1758) (Decapoda, Nephropidae), in the Tyrrhenian Sea (NW Mediterranean), were evaluated using time‐series data (1994–2008) from experimental trawl surveys and commercial landings. The influence of several environmental variables (sea surface temperature, wind‐mixing index and NAO index) and fishing effort indices (number of days at sea per month and mean engine power of the trawl fleet) were investigated. The time series were analysed by means of min/max auto‐correlation factor analysis (MAFA) and dynamic factor analysis (DFA). The abundance of P. longirostris showed a clear increasing trend, significantly correlated with the fishing effort index (number of days at sea per month), the sea surface temperature and the wind‐mixing index. The temporal variations in the stock of P. longirostris , which has a preference for warm waters, were positively correlated with the rise of the sea surface temperature and the decrease of wind circulation. For N. norvegicus , an increasing trend of landings per unit of effort and recruitment index contrasted with a decreasing trend of relative population abundance (biomass and density indices).

Food resource partitioning in a Mediterranean demersal fish assemblage: the effect of body size and niche width - Francesco Colloca; Paolo Carpentieri; Elena Balestri; Giandomenico Ardizzone (Marine Biology, 2010)

Rhythms of feeding activity and food consumption of two Mediterranean burrowing fishes: Gnathophis mystax (Delaroche) and Chlopsis bicolor Rafinesque - Paolo Carpentieri; Francesco Colloca; Giandomenico Ardizzone (Marine Ecology, 2007)
Data on the food consumption, feeding activity and periodicity of two burrowing fish, the congrid eel Gnathophis mystax (Delaroche, 1809) and the false moray Chlopsis bicolor Rafinesque, 1810 are presented. In all, 455 specimens were collected by bottom trawl in the central Mediterranean Sea at depths ranging from 140 to 160 m during four 24‐h day–night sampling cycles. The diet of G. mystax and C. bicolor was investigated by means of stomach content analysis. Diet varied significantly with length and maturity stage. During ontogenetic development G. mystax occupied different trophic levels: diet shifted from amphipods, predominantly in the smaller congrid eels [ 30 cm TL). Before the transition to the icthyophagous phase, the congrid eel showed a more generalistic foraging behaviour where decapods ( Solenocera membranacea , Parapenaeus longirostris , Alpheus glaber ), cephalopods ( Sepiola spp. and Alloteuthis media ), benthic (Gobiidae, Callionymus maculatus, Arnoglossus laterna ) and benthopelagic fish ( Argentina sphyraena ) dominated the diet. Smaller C. bicolor ( A. glaber , Processa canaliculata ) and reptantian ( Medorippe lanata , Goneplax rhomboides ). Daily ration values, computed from the Eggers method, ranged from 2.48% to 2.99% wet body weight for C. bicolor and G. mystax , respectively. Diel patterns in stomach fullness and the trophic niche overlap between the two species were also discussed.